Pengaruh Penerapan Aplikasi e-government Pembayaran Pajak Kendaraan Bermotor Terhadap Kinerja Cash Adminstration (Studi Kasus di Kantor Unit Pelaksana Teknis Dinas Pendapatan Provinsi Jawa Timur Trenggalek) - Sungging Purwokoadi (DIA: Jurnal Administrasi Publik, 2014)
This study entitled "THE EFFECT OF E-GOVERNMENT APPLICATIONS VEHICLE TAX PAYMENTS ON THE PERFORMANCE OF CASH ADMINISTRATION". Revolutionary technology telecommuni-cations, media and information technology (ICT) affects the increasing demands and expectations of the public on fast public service, accurate, and inexpensive but excellent. Democratization, impacting the increasing demands people's participation in public policy, demand transparency, accountability and quality of public performance. Descriptive research is a study of the problems in the form of the current facts of a population which aims to test hypotheses or answer questions relating to the current state of the subject under study. Correlational research is to study the characteristics of the problem in the form of a correlational relationship between two or more variables which aims to determine whether there is an association between two or more variables, as well as how far the correlation that exists between the variables studied. The research method of data with secondary data research types are the type of research data obtained institutional data from the Unit Pelaksana Teknis Dinas Pendapatan Provinsi Jawa Timur through observation, also use this type of research primary data obtained through field surveys. The research sample used all employees serve as responden. The collecting data through observation and questionnaire. Answer the problem formulation used descriptive statistical analysis tool with the help of a frequency table and regression models using SPSS release 16. Hypothesis testing produces, indicating that the hypothesis 1 is accepted, it means the variable partial application of e-Banking System has a positive and significant impact on the performance of Cash Adminstration. The results of hypothesis testing indicates that the hypothesis 2 in this study received, meaning that in partial Revenue Application Implementation (SAP) has a positive and significant impact on the performance of Cash Adminstration Variation of performance can be explained by the Adminstration Cash independent variables of e-Banking System Implementation and Application of Revenue Application (SAP) and while theÂ  explained by other factors. The Performance of Cash Administration will rise properly Implementation of e-Banking System and Application System Application Revenues(SAP) is well managed.